Cardiac amyloid presenting as cardiogenic shock: case series. Issue 7 (26th July 2021) - Oye, Monique; Dhruva, Pooja; Kandah, Fadi; Oye, Melissa; Missov, Emil
Abstract: Background: Amyloidosis is a systemic infiltrative disease that can affect nearly every organ in the human body. It is characterized by the deposition of misfolded protein within various tissues and organs. Once there is cardiac involvement this portends a worse prognosis. Case summary: We describe a case series of two patients with cardiac amyloidosis presenting as a cardiogenic shock. There were several missed opportunities in diagnosing cardiac amyloid prior to their fatal presentations. In the first case, a 65-year-old African-American male patient presented with worsening shortness of breath and signs of heart failure. Echocardiography revealed preserved ejection fraction. He was diagnosed with light chain subtype of cardiac amyloidosis, and rapidly deteriorated during his admission. Patient in the second case is a 75-year-old African-American female who presented with worsening heart failure and hypotension. Echocardiography revealed reduced ejection fraction. She was diagnosed with transthyretin cardiac amyloid. Her clinical status worsened during admission and she went into cardiogenic shock requiring multiple vasopressors. Discussion: This case series discusses two incidences of cardiac amyloidosis presenting as cardiogenic shock in African-American patients. This article postulates that cardiac amyloidosis may be misdiagnosed for more common causes of heart failure especially among this demographic group. Once patients with cardiac amyloid present with cardiogenic shock their clinical course is typically rapidly fatal despite aggressive measures. Earlier detection is imperative to prevent poor outcomes.